2021
DOI: 10.18421/tem103-38
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation of Male and Female Entrepreneurs in Small Firms

Abstract: Many research studies indicate differences in the activities of small enterprises run by female and male entrepreneurs. These differences also apply to shaping entrepreneurial orientation. The main aim of the paper is to identify the entrepreneurial orientation in dimensions of autonomy, innovation, risk-taking, different level of proactivity, and competitive aggressiveness in relation to the gender of the entrepreneurs. This paper presents the results of a survey conducted among 220 small enterprises in Polan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some studies believe that more involved men work better than women [30]. Similarly, several other studies have described gender as an important predictor of entrepreneurial behavior and intensity and revealed that men have more intensity towards entrepreneurship than women [31]. Likewise, many women want academic and personal freedom, but are less able and confident to run a business [32].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Some studies believe that more involved men work better than women [30]. Similarly, several other studies have described gender as an important predictor of entrepreneurial behavior and intensity and revealed that men have more intensity towards entrepreneurship than women [31]. Likewise, many women want academic and personal freedom, but are less able and confident to run a business [32].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The success of SMEs is linked to local economic conditions, as market growth in the SME sector usually occurs at the same pace as the macroeconomy as a whole; therefore, in the event of an economic downturn, SMEs have difficulties (Betáková et al, 2021).…”
Section: H1: Generation Of the Respondent Has An Effect On The Perception Of Attitudes On The Management Of Enterprisementioning
confidence: 99%
“…At the same time, the differences, although statistically significant, were small and could not justify the claim that men and women are fundamentally different regarding entrepreneurship. For example, Betáková et al (2021) found that on a 7-point Likert scale, men scored 0.286 higher than women on "competitive aggressiveness". Performance studies found gender differences (to women's detriment), while several papers found women to be better at some aspects of entrepreneurship.…”
Section: What Did They Find?mentioning
confidence: 99%